Catcalling sebagai Pelecehan Seksual Verbal: Manifestasi Kekerasan Simbolik terhadap Perempuan dalam Ruang Publik (International Forum of Researchers and Lecturers, 2025)
The phenomenon of catcalling is a form of verbal sexual harassment that is often trivialized by society, even though this practice reflects the existence of symbolic power that places women in a subordinate position in public spaces. Catcalling demonstrates the enduring dominance of patriarchal culture, which is embedded through language and actions that appear ordinary yet subtly demean women's dignity. This study aims to describe the forms and characteristics of catcalling, examine catcalling as a manifestation of symbolic violence, and identify the social and psychological impacts experienced by victims. This study uses a descriptive qualitative approach with data collection techniques through direct observation and in-depth interviews with young women at Taman Literasi Blok M. Based on Pierre Bourdieu's theory of symbolic violence, this study concludes that catcalling not only has an emotional impact but also reinforces gender inequality that is internalized in social norms. This practice occurs through a symbolic process that is inherited and normalized in everyday interactions.